2012
DOI: 10.1063/1.3690862
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle tumbling inhibited by inertia

Abstract: International audienceVesicles under flow constitute a model system for the study of red blood cells (RBCs) dynamics and blood rheology. In the blood circulatory system the Reynolds number (at the scale of the RBC) is not always small enough for the Stokes limit to be valid. We develop a numerical method in two dimensions based on the level set approach and solve the fluid/membrane coupling by using an adaptive finite element technique. We find that a Reynolds number of order one can destroy completely the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 17 publications
(7 reference statements)
7
51
1
Order By: Relevance
“…In that previous work, it was shown that a vesicle that should be tumbling in a viscous flow will tank-tread when the Reynolds number is increased. More recently Laadhari, Saramito & Misbah (2012) have observed similar behaviour.…”
Section: Introductionsupporting
confidence: 60%
“…In that previous work, it was shown that a vesicle that should be tumbling in a viscous flow will tank-tread when the Reynolds number is increased. More recently Laadhari, Saramito & Misbah (2012) have observed similar behaviour.…”
Section: Introductionsupporting
confidence: 60%
“…For any explored volume fraction φ, η loc is always found to increase with Re. This effect is attributed to the increase of capsule inclination angle due to inertia (in agreement with the work of Laadhari, Saramito & Misbah (2012)): the particles assume a larger cross-section in the channel, which in turn leads to a larger flow resistance, resulting in a higher local viscosity. This led to two conclusions.…”
Section: Overviewsupporting
confidence: 65%
“…(1). At the scale of the RBC the Reynolds number is often small enough (exceptions may occur in the arterioles and at sites of aneurysms, for example, (Laadhari et al, 2012)) so that inertia can be neglected. The vesicle membrane acts on the fluid via bending forces, while the local membrane area remains unstretched; the membrane develops tension forces ζ that prevent extension (or compression).…”
Section: Model and Methodsmentioning
confidence: 99%